A first step toward liposome-mediated intracellular bacteriophage therapy. (September 2015) - Nieth, Anita; Verseux, Cyprien; Barnert, Sabine; Süss, Regine; Römer, Winfried
<x xml:space="preserve">Abstract</x> Objectives: The emergence of antibiotic-resistant bacteria presents a severe challenge to medicine and public health. While bacteriophage therapy is a promising alternative to traditional antibiotics, the general inability of bacteriophages to penetrate eukaryotic cells limits their use against resistant bacteria, causing intracellular diseases like tuberculosis. Bacterial vectors show some promise in carrying therapeutic bacteriophages into cells, but also bring a number of risks like an overload of bacterial antigens or the acquisition of virulence genes from the pathogen. Methods: As a first step in the development of a non-bacterial vector for bacteriophage delivery into pathogen-infected cells, we attempted to encapsulate bacteriophages into liposomes. Results: Here we report effective encapsulation of the model bacteriophage λeyfp and the mycobacteriophage TM4 into giant liposomes. Furthermore, we show that liposome-associated bacteriophages are taken up into eukaryotic cells more efficiently than free bacteriophages. Conclusion: These are important milestones in the development of an intracellular bacteriophage therapy that might be useful in the fight against multi-drug-resistant intracellular pathogens like Mycobacterium tuberculosis.